The figuration of action in internship reports: language, writing and action in the context of initial teacher training - Gurgel, Manoelito Costa (2020)
In this article, in the area of Applied Linguistics, we propose to analyze, based on the theoretical-methodological foundations of Sociodiscursive Interactionism (BRONCKART, 2008, 2009), how native Portuguese-speaker teachers, in initial formation, discursively represent, in internship reports,    theirs actions in the activities of teaching and how the process of figuration of action, mediated in this case by writing, contributes to the formation and professional development of teachers. In order to do this, we analyzed the action figures (BULEA, 2010) that three pairs of trainees from the course of Letters of the Federal University of Ceará mobilized to represent, in internship reports, their actions in teaching activities. From the segmentation of fragments from thematic and enunciative-discursive criteria, we identified the occurrences of action figures in the three reports. In our analysis, we observed the predominance of past action action figures, which, mobilized in segments of relative interactive, present a retrospective apprehension of the action understood in its uniqueness. The almost totality of this figure in the reports analyzed indicates that the trainees were more interested in reporting the tasks performed, without reflecting, however, on, for example, the validity and productivity of the reported procedures.